Infrastructure, trade facilitation, and network connectivity in Sub-Saharan Africa - Benjamin Shepherd (Journal of African Trade, 2016)
This paper uses new measures of value added in exports in two sectors (textiles and clothing, and agriculture) to examine the linkages between trade facilitation and infrastructure on the one hand, and value chain participation on the other. It applies network analysis methods to derive a summary measure of value chain connectivity for 189 countries, including 44 in Sub-Saharan Africa. There is a statistically significant association between this measure and summary indicators of infrastructure development and trade facilitation performance. Moreover, it is not only a country's own performance that matters, but also that of its neighbors. The regional dimension of infrastructure and trade facilitation policies is an important determinant of particularly SSA countries' ability to connect to global value chains.
Keywords: 330; Trade; Global value chains; Connectivity; Infrastructure; Trade facilitation; Sub-Saharan Africa